Trends of seed production, varietal scenario and future prospects in barley - Goyal, Vishnu Kumar; Kumar, Lokendra; Kharub, Ajit Singh (Journal of Cereal Research, 2017)
After considering past ten years indent and production trends, it was observed that the seed indents during 2014-15 were three folds higher than 2005-06, while the production was increased by 34 per cent over 2005-06, respectively. During 2014-15, the placed indents were higher of 7.42 and 24.16 per cents over the previous years i.e. 2012-13 and 2013-14, respectively. The number of indented varieties ranged from 22 to 39 in barley breeder seed chain. On the basis of last three years, it was depicted that the seed indents for six-row feed barley varieties namely RD2660 and JB58 were increased tremendously i.e. two and five times, respectively. Similarly, the indents of salinity/alkalinity and hulless varieties namely NDB1173 and NDB943 were also increased two and four times, respectively. An increase of 36.7 per cent was also exhibited for two-row malt barley variety DWRUB52, whereas, another malt barley variety DWRB91 also became popular during 2014-15 and 2015-16 and indented in higher quantities. The rainfed barley variety RD2660 showed increase during 2012-13 (65.00 q), 2013-14 (110.00 q) and 2014-15 (238.00 q), respectively.Â  It is anticipated that in NWPZ, in future newly released malt barley varieties as DWRB92 and DWRB101 (both timely sown) and DWRB91 (late sown) will find still higher places in indent due to their better malting quality and raw material demand from the brewing and malting industries.Â DOI:10.25174/2249-4065/2017/70102